Sleepover - Nussbaum, Joe, 1973-; Vega, Alexa; Boorem, Mika.; Lynch, Jane.; Huntington, Sam, 1982- ([United States] : MGM Home Entertainment, 2004)
When Julie and her best friends throw a sleepover to celebrate the end of junior high, they unexpectedly find themselves challenged to an all-night scavenger hunt. A challenge issued by the most popular girls in school. The girls end up hijacking one of the Dad's cars, sneaking into a club, boosting a cute boys' boxer shorts, and even crashing the high school's prom. It's all part of the fun.
Special features: audio commentary by director Joe Nussbaum and cast; "A guide to the perfect sleepover" making-of featurette; "Meet the girls" actress profiles; "Ready, set, action!" featurette; 'Sleepover' confessions; gag reel; behind-the-scenes photo gallery; original theatrical trailer.
Director of photography, James L. Carter ; editor, Craig P. Herring ; music, Deborah Lurie ; costume designer, Pamela Withers Chilton ; production designer, Stephen McCabe.
Alexa Vega, Mika Boorem, Jane Lynch, Sam Huntington, Sara Paxton, Brie Larson, Scout Taylor-Compton, Douglas Smith, Katija Pevec, Steve Carell, Jeff Garlin.
DVD, region 1, widescreen (1.85:1) presentation; Dolby Digital 5.1 surround.
English, dubbed French or dubbed Spanish dialogue, Cantonese, English, French, Mandarin or Spanish subtitles; closed-captioned.
Keywords: Treasure hunt (Game) -- Drama; Sleepovers -- Drama; Teenage girls -- Drama